Implementasi Smart Home pada Platform Apple Homekit dan Google Home dengan Raspberry Pi 4B - Abdul Jabbar Robbani; Fifi Alfiaturrohmah; Maulana Rafi Nurdiansyah; Amanda Salsabila Maharani; Aditya Dwi Putro (Sekawan Institut, 2024)
This research examines the significant impact of technological advances, especially in the Internet of Things (IoT) paradigm, on various aspects of human life strongly manifested during the In-dustrial Revolution Era 4.0. The main focus of this research is on the application of advanced and innovative IoT concepts in the context of smart homes, integrating popular platforms such as Apple HomeKit and Google Home. The temperature sensor (DHT11) and light sensor (LDR) play a key role as important input elements, enabling the optimization of smart home automation functions. Raspberry Pi 4B was chosen as the main platform, the